Analyzing the Purbaya Effect: A Descriptive Qualitative Study on Fiscal Policy and Economic Growth in Indonesia - Jan Horas Veryady Purba (Westscience Press, 2026)
This study examines the phenomenon of the Purbaya Effect within the framework of Indonesia’s fiscal policy, focusing on its implications for market dynamics, economic growth, and fiscal credibility. Addressing a research gap in the limited academic discourse on the Purbaya Effect—with prior studies largely confined to general fiscal issues such as deficits and government spending—this research adopts a descriptive qualitative approach. Two articles were analyzed using NVivo to identify dominant themes and word frequencies. Findings reveal that the Purbaya Effect signifies a paradigm shift toward expansionary fiscal strategies, characterized by increased government spending, interest rate reductions, liquidity injections, and the strengthening of MSMEs and the real sector as drivers of growth. Thematic analysis highlights the dominance of terms such as economy, consumption, fiscal, investment, and financing, underscoring the role of fiscal policy as an economic accelerator. Strategically, the Purbaya Effect shapes market perceptions, public expectations, and fiscal credibility, while opening pathways for long-term development through infrastructure investment and human capital enhancement. Nonetheless, expansionary fiscal measures carry risks of inflation, budget deficits, and crowding out, necessitating cross-sectoral coordination and macroprudential oversight. This study contributes to macroeconomic literature by introducing a novel conceptual lens and offers practical insights for designing inclusive, credible, and sustainable fiscal policy in Indonesia.